2009
DOI: 10.1074/jbc.m808176200
|View full text |Cite
|
Sign up to set email alerts
|

Independent β-Arrestin2 and Gq/Protein Kinase Cζ Pathways for ERK Stimulated by Angiotensin Type 1A Receptors in Vascular Smooth Muscle Cells Converge on Transactivation of the Epidermal Growth Factor Receptor

Abstract: Recent studies in receptor-transfected cell lines have demonstrated that extracellular signal-regulated kinase (ERK) activation by angiotensin type 1A receptor and other G protein-coupled receptors can be mediated by both G protein-dependent and ␤-arrestin-dependent mechanisms. However, few studies have explored these mechanisms in primary cultured cells expressing endogenous levels of receptors. Accordingly, here we utilized the ␤-arrestin biased agonist for the angiotensin type 1A receptor, SII-angiotensin (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
118
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 109 publications
(130 citation statements)
references
References 42 publications
(43 reference statements)
10
118
0
2
Order By: Relevance
“…EGFR-dependent outputs emanating from this domain activate at least two discrete signaling axes (6). One is represented by Erk1/2 and its downstream targets and another involves activation of p38 MAPK, PDK1, Akt, and p70S6K (7,8). This complexity of the AT1R signaling repertoire was anticipated by early findings in which we showed that Ang II stimulation of phospholipase-mediated generation of diacylglycerol is biphasic in VSMCs.…”
mentioning
confidence: 65%
“…EGFR-dependent outputs emanating from this domain activate at least two discrete signaling axes (6). One is represented by Erk1/2 and its downstream targets and another involves activation of p38 MAPK, PDK1, Akt, and p70S6K (7,8). This complexity of the AT1R signaling repertoire was anticipated by early findings in which we showed that Ang II stimulation of phospholipase-mediated generation of diacylglycerol is biphasic in VSMCs.…”
mentioning
confidence: 65%
“…Cells were split and used for assays 48 h after transfection. For rVSMCs, 80-90% confluent early passage (<3) VSMCs were transfected with siRNA using Lipofectamine 2000 transfection reagent (Invitrogen) according to the modified manufacturer's instructions (37). The siRNA sequence targeting β arrestin1 was 5-AGCCUUCUGUGCUGA-GAAC-3, corresponding to position 431-459 relative to the start codon.…”
Section: Methodsmentioning
confidence: 99%
“…1 Sar,4 Ile, 8 Ile-angiotensin II (SII) induces ␤-arrestin recruitment, receptor internalization, and ␤-arrestin-mediated signals without activating G protein coupling (Wei et al, 2003;Ahn et al, 2004;Kim et al, 2009). Unfortunately, this peptide displays low receptor binding affinity (Holloway et al, 2002), which has made in vivo characterization of its effects challenging.…”
Section: Introductionmentioning
confidence: 99%